(untitled) (Journal of Economic Research & Business Administration, 2015)
This article discusses this problem as"" credit debt of the Republic of Kazakhstan banks. ""About what is currently the situation in the commercial banks of the second level of our country, in numbers the real debt of banks listed and how they came to this state, and where all this may result in the near future. Also, a table for a better view, the condition of the commercial banks of the Republic of Kazakhstan.